Meningkatkan Minat Belajar Anak-Anak Panti Asuhan Melalui Pembelajaran Bahasa Inggris - Yulia Ramadani; Husni Tamrin (Yayasan Literasi Sains Indonesia, 2023)
Interest in learning is a person's tendency towards something he wants and creates a feeling of pleasure about that something. Interest is very influential on the achievements achieved, people who do not have an interest in a job, it is impossible to master it properly. If someone feels something is profitable for him then his interest will be higher, and it can bring satisfaction from within, if someone feels dissatisfied, then interest in something will also decrease. If the interest is ingrained in the student, the willingness to learn will drastically arise by itself. . Interest in learning means that if someone is interested in a lesson, he will have a feeling of interest in that lesson. He will study diligently and continue to understand all the knowledge related to that field, he will follow the lessons enthusiastically and without any burden on him. Like the children at the Shade of Kasih Kemuliaan Orphanage, they want to increase their interest in learning, especially in English lessons. And really need help to increase their interest in learning. The process of providing this assistance was carried out in the PKL 2 mini project activities, namely by using the Groupwork method as a social work technical approach aimed at helping individuals who experience problems with face-to-face services. Several stages consist of Assessment, Program Planning, Intervention, Program Evaluation and the last stage is Termination. The focus of solving client problems is to convince the client to be even more active in the learning process. The purpose of this strategy was declared successful with significant client changes including in the learning process which increased interest in learning for him.